2011
DOI: 10.1002/eji.201040862
|View full text |Cite
|
Sign up to set email alerts
|

Telomere‐dependent replicative senescence of B and T cells from patients with type 1a common variable immunodeficiency

Abstract: A subset of patients with common variable immunodeficiency (CVID), group 1a of the Freiburg classification, is characterized by increased B cells expressing low levels of CD21 (CD21 low ), lymphoproliferation and autoimmunity. The CD21 low B cells have been shown to be profoundly anergic, and defects of BCR-mediated calcium signaling and of T cells have been described in CVID 1a. We found that also the classical naïve B cells from CVID 1a patients, but not from CVID non-1a patients, proliferated poorly. The B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…Clonal B cells of MC commonly secrete a natural antibody bearing an idiotype, encoded by the V H 1-69 variable gene, which has rheumatoid factor activity and cross-reacts with the E2 protein of HCV [1]. The V H 1-69-expressing B cells of MC patients can be subdivided into two major populations [2][3][4][5], one with the phenotype of normal human marginal zone (MZ) B cells (IgM + IgD + CD27 + CD21 + ), and one with the phenotype of the CD21 low innate-like B cells that are expanded in common variable immunodeficiency [6][7][8], in rheumatoid arthritis [7] and in human immunodeficiency virus infection [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clonal B cells of MC commonly secrete a natural antibody bearing an idiotype, encoded by the V H 1-69 variable gene, which has rheumatoid factor activity and cross-reacts with the E2 protein of HCV [1]. The V H 1-69-expressing B cells of MC patients can be subdivided into two major populations [2][3][4][5], one with the phenotype of normal human marginal zone (MZ) B cells (IgM + IgD + CD27 + CD21 + ), and one with the phenotype of the CD21 low innate-like B cells that are expanded in common variable immunodeficiency [6][7][8], in rheumatoid arthritis [7] and in human immunodeficiency virus infection [9].…”
Section: Introductionmentioning
confidence: 99%
“…The CD21 low B cells expanded in HIV infection and in common variable immunodeficiency are functionally exhausted, as they fail to proliferate in response to the stimulation of the B cell receptor (BCR) and of CD40 as well as of the innate Toll-like receptors (TLR) 9 and 7 [6][7][8][9]. Recently, the CD21 low V H 1-69-expressing B cells expanded in HCV-associated MC have been reported to be functionally anergic, and it was suggested that their counterparts could be normally functioning [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…We found that, immediately after IVIG infusion, the number of circulating B cells decreases. Interestingly, after IVIG infusion, circulating B cells display a decrease in the expression of CD21, thus becoming similar to the functionally exhausted CD21 low B cells that spontaneously accumulate in some CVID patients [18][19][20] and in patients with HIV infection [21] or mixed cryoglobulinemia [22,23]. Our data suggest that IVIG therapy induces in vivo the B cells of CVID patients to differentiate into CD21 low B cells primed to undergo apoptosis.…”
Section: Introductionmentioning
confidence: 63%
“…CD21 low B cells were defined as CD20 ? cells with CD21 mean fluorescence intensity (MFI) below the threshold seen in mature B cells of CVID patients and of healthy donors [20]. The proportions of apoptotic cells were assessed by staining with annexin V and 7-aminoactinomycin D (7-AAD); annexin V-positive/7-AAD negative cells were classified as early apoptotic, and annexin V-positive/7-AAD positive cells as late apoptotic.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation